THE EFFECT OF GAME SUITS ON STUDENT MOTIVATION AND LEARNING OUTCOMES ON SUMMATION MATERIAL - Mira Amelia; Isrok'atun; Dety Amelia Karlina (Jurnal Cakrawala Pendas, 2024)
This research was motivated by the paradigm of grade II students who consider counting difficult. The fact found in the field is that the learning pattern is not fun so that students do not like and are not motivated to learn mathematics. The purpose of this study was to find out how game suits affect student motivation and their learning outcomes about addition in grade II. In addition, this study also determined whether game suits help students in improving students' numeracy skills related to summation operations. This study used quasi-experimental research with a non-equivalent control group design. The sample in this study was grade II students totaling 60 students. The motivation data collection technique is questionnaire, while learning outcome data is pretest and posttest. Data analysis techniques are performed using SPSS 23 for windows with t-test. The results of this study show that game suits in mathematics learning activities on addition material have a significant effect on increasing student learning motivation and have a significant effect on improving student learning outcomes.